A Comparison of the Accuracy of Parts-of-Speech Tagging Systems Based on a Mathematical Model. Issue 3 (3rd July 2019) - Vulanović, Relja; Mosavi Miangah, Tayebeh
Abstract: Formulae are proposed for measuring the efficiency of part-of-speech tagging systems. The efficiency is a modification of tagging accuracy, which enables the comparison of tagging systems in the situation when they are applied to different corpora and/or use different tag-sets. The approach is based on a mathematical model of tagging accuracy and genotypes.